Design of Micro-perforated PTFE mould for manufacture of Paneer, Cheese and Tofu using Finite Element Analysis: Design of Micro-perforated PTFE mould - Jayanth K J; Dr. Mahesh Kumar G (Indian Journal of Dairy Science, 2023)
The idea of utilizing a micro-perforated PTFE (polytetrafluoroethylene) mould to manufacture paneer, cheese, and tofu was conceived and mould was designed, developed and tested. The micro-perforated PTFE mould is intended to work at extreme temperature 65 and 110ºC, 200 kPa inside pressure. This new generation pressing mould contains micro perforations of 300µm diameter which are drilled using advanced high precision 4 and 3 axis CNC machines. There will be failure (due to induced hoop stress) in the mould when Von Mises(equivalent) stress generated is more than yield stress of virgin PTFE (30 MPa). Wall thickness of mould was optimized by Finite Element Analysis (FEA) by hyper tetrahedron meshing using ANSYS- 22. The results obtained from stress analysis will be expressed as Von Mises stress, deformation and factor of safety.  A design software developed by ASME was employed to validate shell thickness. The model prediction was shown to be in good agreement with the analytical calculation. Micro-perforated PTFE mould was fabricated as per FDA, c-GMP standards from 6.00 mm thick virgin PTFE material. The FEA resulted in Von Mises Stress of 14.7 MPa, deformation of 2.1535×10-10 m and factor of safety of 2.04. The working drawings were developed and actual fabrication was carried out adopting the prescribed sanitary standards. Satisfactory production of paneer was carried out in the newly designed and developed PTFE paneer mould resulted in excellent quality product.